Positioning academic partners to align with proper modes of university-industry collaboration - Nisit Manotungvorapun (2022)
Nowadays, many firms attempt to advance their technological capabilities by engaging with universities in various activities ranging from training programs to researcher exchanges, research contracts and R&D collaboration. The effectiveness of these activities is greatly affected by complementarity and compatibility between a firm and an academic institute. Thus, the determination of academic partners' characteristics becomes essential. This study focuses on the key managerial challenge of how to put the right academic partner into the right form of collaborative activities. By assessing the degree of complementarity and compatibility of academic partners, the analysis result can be offered in four modes of collaborations: orchestrated, assistive, attentive and mismatched collaborations. The managerial recommendations for each mode of collaboration are also provided in the discussion.